Changes in Maternal Gene Expression in Olfactory Circuits in the Immediate Postpartum Period - Canavan, Sofija V.; Mayes, Linda; Treloar, Helen B. (Frontiers in Psychiatry, 2011)
Regulation of maternal behavior in the immediate postpartum period involves neural circuits in reward and homeostasis systems responding to cues from the newborn. Our aim was to assess one specific regulatory mechanism: the role that olfaction plays in the onset and modulation of parenting behavior. We focused on changes in gene expression in olfactory brain regions, examining nine genes found in previous knockout studies to be necessary for maternal behavior. Using a quantitative PCR (qPCR)-based approach, we assessed changes in gene expression in response to exposure to pups in 11 microdissected olfactory brain regions. Over the first postpartum days, all nine genes were detected in all 11 regions (at differing levels) and their expression changed in response to pup exposure. As a general trend, five genes (Dbh, Esr1, FosB, Foxb1, and Oxtr) were found to decrease their expression in most of the olfactory regions examined, while two genes (Mest and Prlr) were found to increase expression. Nos1 and Peg3 levels remained relatively stable except in the accessory olfactory bulb (AOB), where greater than fourfold increases in expression were observed. The largest magnitude expression changes in this study were found in the AOB, which mediates a variety of olfactory cues that elicit stereotypic behaviors such as mating and aggression as well as some non-pheromone odors. Previous analyses of null mice for the nine genes assessed here have rarely examined olfactory function. Our data suggest that there may be olfactory effects in these null mice which contribute to the observed maternal behavioral phenotypes. Collectively, these data support the hypothesis that olfactory processing is an important sensory regulator of maternal behavior.